Perencanaan Forest Resort dengan Pendekatan Ekologis di Kawasan Ibu Kota Nusantara (IKN) Kabupaten Penajam Paser Utara, Kalimantan Timur - Vernanda Situngkir, Angelia; Wilfritsz Soaduon Panjaitan, Tigor (Rifa'Institute, 2023)
The New Capital City of Indonesia or IKN which was inaugurated in East Borneo by President Joko Widodo became one of the events awaited by not only the local community, but the people of the archipelago and abroad. The event caused an increased tourist attraction. Therefore, through that event, the increasing need for accommodation facilities that must be available is one of the long-term needs. There will be an increase in tourist visits to IKN with the aim of visiting the Zero Point of IKN or to the Presidential Palace and to surrounding attractions, both water tourism and forest tourism in Borneo. Therefore, through this research, Forest Resort is one form of effort to meet the needs of accommodation facilities for domestic and foreign tourists. The purpose of this design is to create lodging while still carrying out the first principle in IKN, namely Forest City by harmonizing principles through the application of natural and cultural atmosphere that has been given by the environment without the need to damage it. By emphasizing the importance of preserving the environment through public awareness but still being able to enjoy it. With serious implementation, it is expected to reduce the risk of excessive tree cutting in Kalimantan Forests.